Parents’ and healthcare professionals’ experiences and perceptions of parental readiness for resuscitation in Iranian paediatric hospitals: a qualitative study - Hadi Hassankhani; Arezoo Ghavi; Kelly Powers; Mohammad Arshadi-Bostanabad; Hossein Namdar Areshtanab; Mohammad Heidarzadeh (BMJ Open, 2022)
Objective The aim of this study was to examine parents’ and healthcare professionals’ experiences and perceptions of parental readiness for resuscitation of their child in a paediatric hospital.Design This exploratory descriptive qualitative study used content analysis. Participants shared their experiences and perceptions about parental readiness for cardiopulmonary resuscitation through semi-structured and in-depth interviews. MAXQDA 2020 software was also used for data analysis.Setting The setting was two large teaching paediatric hospitals in Iran (Este Azerbaijan and Mashhad).Participants Participants were 10 parents and 13 paediatric healthcare professionals (8 nurses and 5 physicians). Selection criteria were: (a) parents who experienced their child’s resuscitation crisis at least 3 months prior and (b) nurses and physicians who were working in emergency rooms or intensive care wards with at least 2 years of experience on the resuscitation team.Results Participants shared their experiences about parental readiness for resuscitation of their child in four categories: awareness (acceptance of resuscitation and its consequences; providing information about the child’s current condition and prognosis), chaos in providing information (defect of responsibility in informing; provide selective protection of information; hardness in obtaining information), providing situational information (honest information on the border of hope and hopeless; providing information with apathy; providing information as individual; dualism in blaming; assurance to parents; presence of parents to better understand the child’s situation) and psychological and spiritual requirements (reliance on supernatural power; need for access to a psychologist; sharing emotions; collecting mementos).Conclusion The results of this study provide insight on the needs of parents and strategies to use to prepare them for their child’s resuscitation crisis, which can be used to enhance family centred care practices in paediatric acute care settings.